2021
DOI: 10.3390/genes12081132
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of 15 Antisense Long Non-Coding RNAs in Osteosarcoma

Abstract: The human genome encodes thousands of natural antisense long noncoding RNAs (lncRNAs); they play the essential role in regulation of gene expression at multiple levels, including replication, transcription and translation. Dysregulation of antisense lncRNAs plays indispensable roles in numerous biological progress, such as tumour progression, metastasis and resistance to therapeutic agents. To date, there have been several studies analysing antisense lncRNAs expression profiles in cancer, but not enough to hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 75 publications
0
24
0
Order By: Relevance
“…It was reported that HIF1A-AS2 is up-regulated in GC tumorous tissues, and its overexpression promotes gastric cancer cell proliferation and metastasis and indicates poor prognosis ( Mu et al, 2021 ; Chen et al, 2015 ). RP11-366L20.2, also known as HMGA2-AS1, has been recognized as an oncogene in pancreatic cancer ( Ros et al, 2019 ) and osteosarcoma ( Rothzerg et al, 2021 ). However, there are few studies on the role of RP11-366L20.2 in gastric cancer, and it is worthy of further study.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that HIF1A-AS2 is up-regulated in GC tumorous tissues, and its overexpression promotes gastric cancer cell proliferation and metastasis and indicates poor prognosis ( Mu et al, 2021 ; Chen et al, 2015 ). RP11-366L20.2, also known as HMGA2-AS1, has been recognized as an oncogene in pancreatic cancer ( Ros et al, 2019 ) and osteosarcoma ( Rothzerg et al, 2021 ). However, there are few studies on the role of RP11-366L20.2 in gastric cancer, and it is worthy of further study.…”
Section: Discussionmentioning
confidence: 99%
“…Hence it is important to understand and correlate expression of MCTs and ECMs in different compartments. Our analysis revealed nine differentially expressed MCT genes in both stromal and epithelial samples including the upregulated thyroid hormone (TH) transporters MCT8 (SLC16A12) and MCT10 (SLC16A10), monocarboxylate transporter MCT2 (SLC16A7), MCT6 (SLC16A5) with potential role in glucose and lipid metabolism, and an lncRNA SLC16A1-AS1 previously identified as a prognostic or diagnostic biomarker in a number of cancers [13,[47][48][49][50][51][52][53][54]. To our knowledge, the upregulation of the TH transporters in the stromal-epithelial samples has not been highlighted previously.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, better understanding of the molecular mechanisms involved in contribution of THs to pancreatic cancer is needed. The lncRNA SLC16A1-AS1 has previously been found to be upregulated in osteosarcoma, glioblastoma and oral squamous cell carcinoma [50, 52, 63], downregulated in non-small cell lung cancer and cervical squamous cell carcinoma [19, 49], and show conflicting expression profile in hepatocellular carcinoma [51, 53, 54]. This is the first study highlighting differential expression of SLC16A1-AS1 in PDAC showing lower levels of expression in epithelial relative to stromal compartment.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it is important to understand and correlate the expression of MCTs and ECMs in different compartments. Our analysis revealed nine differentially expressed MCT genes in both stromal and epithelial samples, including the upregulated thyroid hormone (TH) transporters MCT8 ( SLC16A12 ) and MCT10 ( SLC16A10 ), monocarboxylate transporter MCT2 ( SLC16A7 ), MCT6 ( SLC16A5 ) with a potential role in glucose and lipid metabolism, and an lncRNA SLC16A1-AS1 previously identified as a prognostic or diagnostic biomarker in a number of cancers [ 20 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ]. To our knowledge, the upregulation of the TH transporters in the stromal–epithelial samples has not been highlighted previously.…”
Section: Discussionmentioning
confidence: 99%